A comparative study of fruit and vegetable consumption and its association with metabolic risk factors for non communicable diseases among rural and urban males in Zimbabwe - Manyeruke, Norman; Vermaak, Kerry; Nunu, Wilfred Njabulo; Mudonhi, Nicholas (Frontiers in Nutrition, 2025)
PurposeConsumption of fruits and vegetables reduces the prevalence of metabolic risk factors for NCDs. No studies assessing the relationship between fruit and vegetable consumption and metabolic risk factors for NCDs have been done in Zimbabwe. This study focused on the comparison of the consumption of fruits and vegetables between rural and urban settings and their relationships with metabolic risk factors for NCDs and demographic variables.MethodsA sample of 400 males was obtained from the two provinces, i.e., 200 men from Bulawayo (urban) and Mashonaland East (rural). The fruits and vegetables were measured using the World Health Organisation (WHO) stepwise questionnaire, which was translated in the Zimbabwean context.ResultsThe overall consumption of fruits and vegetables to the recommended level of 5 servings per day was 12. 1% (95 CI = 9.0–15.4). There were more people in rural settings (15.3, 95% CI 11.6–18.4) meeting the WHO recommended level of consumption of five servings of fruits and vegetables than urban settings (3.5, 95% CI 1.0–6.3; p < 0.001). The rural group had higher odds of having normal blood glucose level than the urban group (OR = 2.698; 95% CI = 1.796–4.053, p < 0.001). There was a 0.142-unit decline in blood glucose after adjusting for vegetable consumption (−0.142; 95% CI = −0.345 – −0.122, p < 0.033).ConclusionRural respondents consumed more vegetables and fruits than the urban respondents. The consumption of fruits and vegetables was associated with a decrease in blood glucose. There is a need for campaigns to educate the public on the importance of fruit and vegetable consumption to ensuring that dietary intake of fruits and vegetables is significantly improved.